Effect of CNP additive to diluents during capacitation on live percentage and pH of bull epididymal spermatozoa. - J. Ghafil, Mohammedali; W. Zaid, Nazih; S. Ibrahim, Najlaa; F. Nema, Hayder (International Journal of Psychosocial Rehabilitation, 2024)
Abattoir male gonads specimens were collected from Al-Shoáalla abattoir from June 2019 until November 2019 in an average of 2 visits per week. This study was designed to evaluate the optimum effect of C-type natriuretic peptide on the caudal epididymal spermatozoa characteristics from a healthy slaughter bull. Dissected and separated the epididymis from the entire testicle made by a small scissor. The caudae were injected with 5-8 ml of the TCM199 media containing 100 IU/ml penicillin-streptomycin and 100 IU/ml Nystatin using an 18 gauge needle attached toa 5-ml syringe then aspirated. After collection of Spermatozoa samples of cauda epididymis were evaluated under the light microscope has individual motility less than 70% of were rejected. The caudal epididymal Spermatozoa samples transported from petri dish to a 10 ml test tube containing 2 ml maturation media (TCM199) that contain 100 IU/ml penicillin-streptomycin and 100 IU/ml Nystatin; the test tube incubated in a 5% CO2 incubator at 39 Cº for 4 hours for sperm maturation, the presence of distal protoplasmic droplet was the criteria of sperm maturation. Then the samples divided into three equal groups control one, low concentration 10-7 mol/L, and high concentration 10- 6 mol/L. It evaluated the effect of C-type natriuretic peptide (CNP) during capacitation on the live percentage and pH of bull epididymal spermatozoa. The live percentage and pH of sperm were analyzed at 5 min, 10 min, 15 min, 30 min, 45 min, 60 min, 120 min, and 180 min for each group. A total of 20 caudal epididymides were studied during the period of the experiment. Evaluation of spermatozoa parameters as a stained smear for dead and alive spermatozoa was conducted in addition to pH; all results were recorded. The pH of the semen was measured immediately after the recovery of sperms from the epididymal by using a pH litmus paper. A drop of sperms suspension on a glass slide, a drop of Eosin-Negrosin stain was added and mixed. Two smears of each sample were made when each smear dry it was mounted immediately under coverslip using DPX; 200- 400 sperms were examined in each smear on a light heated stage microscope at 40x objective power. The final percentage was calculated by taking the average of two smears. The results of herein study of live percentage in bull epidydimal sperm during the capacitation of control group indicate that the significant changes at the level of (P<0.05) in the control group started within 30 minutes after capacitation while the significant changes starting at level (P<0.05) in low (10-7) mol/L and high (10-6) mol/L concentration with 45 minutes after capacitation to the end of the experiment as well as there were no significant differences between the three studied groups. In contrast, the results of a novel study of pH in bull epidydimal sperm during the capacitation of the control group indicate that the significant changes of pH at the level of (P<0.05) begins within 10 minutes after capacitation while the significant changes starting at level (P<0.05) in low and high concentration with 45 minutes after capacitation to the end of the experiment. At the same time, there were significant differences (P<0.05) between low and high concentration with the control group recorded during the period 45 minutes and lasted until the end of the experiment. The conclusion that there were no changes between control and treated groups in live percentage, and also there was a positive improvement in treated groups in live and pH after capacitation with CNP additive to epididymis sperms.